Cosmos as a Divine Text: Reconstruction of the Epistemology of Qur'anic Interpretation Based on Modern Astrophysics - Abid Nurhuda; Muhammad Hariyadi; Thariq Aziz; Nur Muhammad Lathif (Islamic Religious Education Departement, 2026)
This article discusses the cosmos as a divine text by reconstructing the epistemology of Qur'anic interpretation in light of modern astrophysics. This approach emphasizes the integration of revelation, empirical observation, and philosophical reflection in understanding the phenomena of the universe. By examining Qur'anic cosmological verses hermeneutically and linking them to contemporary astrophysical discoveries, such as stellar evolution, black holes, cosmic background radiation, and the large-scale structure of the universe. The method used is qualitative with a philosophical hermeneutic approach model, where the primary sources are cosmological verses such as (Q.S. Ali 'Imran: 190), (Q.S. Yasin: 40), (Q.S. al-Dzariyat: 47), (Q.S. al-Anbiya’: 30), (Q.S. al-Qamar: 49), (Q.S. al-Hadid: 4), to (Q.S. al-Furqan: 59). The secondary sources are journals, books, or other relevant research. After the data is collected, a comparative thematic content analysis is conducted using a triangulation model to ensure data validity, and conclusions are drawn. The study's results indicate that revelation and science complement each other in building a holistic, transdisciplinary, and relevant understanding of modern science. The proposed Integrative Cosmological Interpretation Model combines the bayani (textual), burhani (rational-empirical), and irfani (spiritual-intuitive) approaches, so that Qur'anic interpretation is not only descriptive, but also prescriptive, philosophical, and ethical. The epistemic and philosophical implications of this research open new perspectives in Qur'anic studies, strengthen the dialogue between science and revelation, and emphasize the cosmos as a medium for human intellectual and spiritual reflection.